O COMPORTAMENTO DO CONSUMIDOR NA ECONOMIA INFORMAL DA REGIÃO DO GRANDE ABC PAULISTA - Ferreira, Rita de Cassia de Andrade (2013)
Reducing the consumption of products that come from the informal economy and educate consumers on what regards to its dangers have been imperative not only for government agencies, but also private organizations and non-governmental institutions that value an improvement business environment. Nonetheless, in spite of the appeal made for consumers not to purchase products from the informal market, numerous informal outlets can be noticed. In this context, this research aims at identifying and analyzing the factors influencing consumer behavior on what concerns products purchased in the informal economy of the Greater ABC Paulista area. To this end, a qualitative study, with an exploratory character, was conducted. Its primary data was collected though semi-structured interviews. Secondary data were obtained through the literature that refers to consumer behavior, considering the following influencing factors: culture, ethics and social responsibility, as well as the informal economy. Subjects who participated in the interviews were economically active people aged between 25 and 44 years old, who consumed products from the informal trade and who were residents in the Greater ABC Paulista area. Based on the results of empirical research is possible to infer that consumers take part in informal trading due to low prices and accessibility to the market place. This is a culturally established consumption due to its widespread presence amongst social networks of which consumers belong. Overall, respondents showed awareness concerning social and environmental harms and ethical issues of the informal economy, yet little is considered at the time of purchase.